Pengenkripsian File Data Pasien untuk Menjamin Kerahasian Informasi Medis - Lie, Gary Melvin; Astuti, Luh Gede (Jurnal Nasional Teknologi Informasi dan Aplikasnya; Vol 2 No 1 (2023): JNATIA Vol. 2, No. 1, November 2023, 2023)
In the era of digitalization of medical information, safeguarding patient data confidentiality has become paramount. This research aims to address the issue of data leakage by implementing file encryption using the AES-128 algorithm. The research methodology encompasses problem identification, system design, testing, and evaluation. The encryption steps of AES-128, namely SubBytes, ShiftRows, MixColumns, and AddRoundKey, are applied to enhance the security of patient data. Testing is conducted using various types of medical data, and an analysis is performed to assess the level of security and algorithm performance. The results indicate that file encryption with AES-128 can provide a high level of security for patient medical information. The AES-128 algorithm generates secure ciphertext that cannot be easily decrypted without the corresponding key. This research contributes to the field of medical information security by implementing AES-128 file encryption in patient data management systems. By enhancing data privacy and security, the utilization of this algorithm has the potential to provide strong protection against data breaches. Further studies can explore the wider application of AES-128 in the context of medical data security and improve algorithm performance.